Influence of Graph Characteristics on Solutions of Feedback Arc Set Problem - Grošelj, Ema Leila; Poljanšek, Tomaž (Proceedings of the10th Student Computing Research Symposium (SCORES’24), 2024)
In this article we present Feedback Arc Set problem and how certain graph characteristics impact the results of heuristic algorithms. We then inspect how the most promising characteristic (treewidth) helps in choosing the most appropriate heuristics for our graph.